Analisis Kinerja Keuangan Sebelum dan Sesudah Right Issue: Studi Empiris pada Perusahaan Go Public yang Melakukan Right Issue Tahun 2021 - Nahar, Aida; Octaviani, Alda (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study aims to analyze financial performance before and after the right issue of shares. The variables analyzed include liquidity, solvency, profitability, activity, and market value ratios. The liquidity ratio uses Current Ratio (CR), the solvency ratio uses Debt to Equity Ratio (DER), the profitability ratio uses Return on Asset (ROA), the activity ratio uses Total Asset Turnover (TATO), and the market value ratio uses Price Earnings Ratio (PER). The sample of this study consists of companies that conducted a rights issue in 2021 and are listed on the Indonesia Stock Exchange, with a total of 7 companies. The company's financial data are from two years and two years after conducting a stock rights issue. Hypothesis testing was carried out using the Wilcoxon Signed Rank Test analysis. The results showed that the Current Ratio (CR), debt-to-equity ratio (DER), Return on Asset (ROA), Total Asset Turnover (TATO), and price-earnings ratio (PER) did not show a significant difference between before and after the stock rights issue activity.